The Relationship Between the Concepts of Hope and Happiness in Students - Leila Ghahremani; Hadi Tehrani; Abdolhalim Rajabi; Alireza Jafari (Iranian Association of Health Education and Health Promotion, 2020)
Background and Objectives: Happiness and hope are two concepts that affect students' mental health. The aim of this study was to determine the relationship between the concept of hope and happiness in students. Materials and Methods: This cross-sectional study was conducted on 250 students in school of health, Shiraz University of Medical Sciences. The data collection tool was Snyder's Hope and MUNSH 's Happiness Questionnaires. Data were analyzed by SPSS version 22 using descriptive and analytical tests including ANOVA, independent samples t-test, Pearson correlation and linear regression. Results: In this study, the mean (±SD) of happiness and hope scores were 4.50 (+0.78) and 24.52 (+0.66) respectively. There was a significant relationship between age (P=0.001) and gender (P=0.008) variables with hope scale. Based on the Pearson correlation coefficient, there was a significant correlation between hope and sub-scales of happiness (Positive affect, negative affect, Positive experience, negative experience) (P<0.001). Results of linear regression analysis showed that, demographic variables, happiness scale and its sub-scales, were able to predict 28.8% of the variations of hope (P<0.001). Conclusion: Therefore, it is necessary that the predisposing factors create psychological problems such as disappointment and depression and etc., identified in students and appropriate educational and counseling programs are being designed and implemented.